2023
DOI: 10.15252/embj.2022112558
|View full text |Cite
|
Sign up to set email alerts
|

Immunity against Moraxella catarrhalis requires guanylate‐binding proteins and caspase‐11‐NLRP3 inflammasomes

Abstract: Moraxella catarrhalis is an important human respiratory pathogen and a major causative agent of otitis media and chronic obstructive pulmonary disease. Toll-like receptors contribute to, but cannot fully account for, the complexity of the immune response seen in M. catarrhalis infection. Using primary mouse bone marrow-derived macrophages to examine the host response to M. catarrhalis infection, our global transcriptomic and targeted cytokine analyses revealed activation of immune signalling pathways by both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 95 publications
1
3
0
Order By: Relevance
“…Unlike human GBP1, our data therefore suggest that mouse GBP1 mechanism of resistance does not result in a direct binding of human GBP1 to LPS 20,31 . Our finding is in line with previous studies on Neisseria meningitidis 32 and Moraxella catarrhalis LOS 45 and E. coli LPS 46 , demonstrating no direct interaction between mouse GBP1 and the LOS.…”
Section: Our Findings Demonstrated That Recognition Of Mdr a Baumanni...supporting
confidence: 93%
“…Unlike human GBP1, our data therefore suggest that mouse GBP1 mechanism of resistance does not result in a direct binding of human GBP1 to LPS 20,31 . Our finding is in line with previous studies on Neisseria meningitidis 32 and Moraxella catarrhalis LOS 45 and E. coli LPS 46 , demonstrating no direct interaction between mouse GBP1 and the LOS.…”
Section: Our Findings Demonstrated That Recognition Of Mdr a Baumanni...supporting
confidence: 93%
“…Lipid A is recognized not only by TLR4 but also by caspase-11, an intracellular LPS receptor (14). Caspase-11 is defined as a non-canonical NLRP3 inflammasome because it not only activates the canonical NLRP3 inflammasome but also induces pyroptosis (gasdermin D-dependent cell death) independent of NLRP3 (27,28). The present study revealed that ALN did not upregulate caspase-11 expression in RAW264 cells but di augment lipid A-induced IL-1β release by caspase-11 knockout RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…THP‐1 monocytes and macrophages were primed using 500 ng/ml ultrapure LPS from E. coli for 3 h. Cells were treated with 36 μg/ml of lecithinase or 10 μM nigericin. For inhibition experiments, THP1 cells were pretreated for 30 min with 20 μM of MCC950 (Enosi Tuipulotu et al , 2023 ). PBMCs were primed using 1 μg/ml Pam3CSK4 (tlrl‐pms, InvivoGen) for 3 h, pretreated with or without 20 μM MCC950 for 30 min, and then stimulated with 1.5 × 10 −3 Units/ml lecithinase or 10 μM nigericin (N7143, Sigma) for 1 h. Cell culture supernatants were collected for ELISA and LDH assays.…”
Section: Methodsmentioning
confidence: 99%